Boy-Wives and Female Husbands : Studies in African Homosexualities. - Murray, Stephen O. (SUNY Press Open Access Series, 2021)
A significant contribution to anthropology, history, and gender studies that reveals the denials of homosexuality in traditional and contemporary African societies to be rooted in colonialist ideologies.